2009
DOI: 10.1159/000189201
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Signaling Pathways Involved in Peptidoglycan-Induced RANTES Production from Murine Langerhans Cells

Abstract: Background: Our previous study showed that percutaneous application of peptidoglycan from Staphylococcus aureus induced eosinophil infiltration in murine skin through production of CCL5/RANTES (regulated upon activation in normal T cells expressed and secreted) from epidermal Langerhans cells. Although it is well known that peptidoglycan is an agonist of Toll-like receptor (TLR)-2, it is unclear whether other TLR agonists are able to induce RANTES production from Langerhans cells. Methods: Langerhans cells wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
0
2
1
Order By: Relevance
“…35 Moreover, findings suggest a role for staphylococcal superantigens in the production of RANTES during the development of atopic skin inflammation. 36 Some studies have suggested a proangiogenic role of IL-6, 4,37 but in our study, we did not find any correlations between IL-6 levels in AD versus healthy individuals.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…35 Moreover, findings suggest a role for staphylococcal superantigens in the production of RANTES during the development of atopic skin inflammation. 36 Some studies have suggested a proangiogenic role of IL-6, 4,37 but in our study, we did not find any correlations between IL-6 levels in AD versus healthy individuals.…”
Section: Discussioncontrasting
confidence: 69%
“…Augmented production of RANTES has correlated with inflammation associated with AD . Moreover, findings suggest a role for staphylococcal superantigens in the production of RANTES during the development of atopic skin inflammation …”
Section: Discussionmentioning
confidence: 96%
“…Polymerase chain reaction (PCR) was performed using a GeneAmp PCR System 9700 (Perkin-Elmer, Norwalk, CT, USA) in a 25-µL reaction volume containing 1.5 µL of cDNA (corresponding to 16 ng of the original mRNA) as described previously, and the PCR products were separated on a 2% agarose gel containing ethidium bromide [7]. The primers used for amplification of β-actin, CXCL9/Mig, CXCL10/IP-10, CCL17/ TARC, CCL22/MDC, TLR2 and NOD2 have been described elsewhere [7,[10][11][12][13][14][15]. The culture supernatants of mast cells were also collected after incubation with PEG and/or MDP for 48 h, and their chemokine concentrations were determined using enzyme-linked immunosorbent assay (ELISA) kits for quantification of murine CXCL10 and CCL17 (R & D Systems).…”
Section: Detection Of Mrna Expression and Quantification Of Chemokinesmentioning
confidence: 99%